Possibly scalable solar hydrogen generation with quasi-artificial leaf approach - Patra, Kshirodra Kumar; Bhuskute, Bela D.; Gopinath, Chinnakonda S. (Scientific Reports, 2017)
Any solar energy harvesting technology must provide a net positive energy balance, and artificial leaf concept provided a platform for solar water splitting (SWS) towards that. However, device stability, high photocurrent generation, and scalability are the major challenges. A wireless device based on quasi-artificial leaf concept (QuAL), comprising Au on porous TiO2 electrode sensitized by PbS and CdS quantum dots (QD), was demonstrated to show sustainable solar hydrogen (490 +/- 25 mu mol/h (corresponds to 12 ml H-2 h(-1)) from similar to 2mg of photoanode material coated over 1 cm(2) area with aqueous hole (S2-/SO32-) scavenger. A linear extrapolation of the above results could lead to hydrogen production of 6 L/h.g over an area of similar to 23 x 23 cm(2). Under one sun conditions, 4.3 mA/cm(2) photocurrent generation, 5.6% power conversion efficiency, and spontaneous H-2 generation were observed at no applied potential (see S1). A direct coupling of all components within themselves enhances the light absorption in the entire visible and NIR region and charge utilization. Thin film approach, as in DSSC, combined with porous titania enables networking of all the components of the device, and efficiently converts solar to chemical energy in a sustainable manner.